2002
DOI: 10.1097/01.mp.0000024147.43288.b1
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid and Reliable Enzyme Immunoassay PCR-Based Screening Method to Identify EBV-Carrying Gastric Carcinomas

Abstract: Epstein-Barr virus (EBV)is associated with a substantial number of gastric adenocarcinomas worldwide, as confirmed by EBER1/2-RNA in situ hybridization (RISH). In the present study, we developed a rapid and sensitive PCR-based prescreening method for the detection of EBV in gastric carcinomas to reduce the amount of laborious EBER1/2-RISH assays to be performed. The method was evaluated by testing gastric adenocarcinomas (n ‫؍‬ 242) using both BamHI W PCR-enzyme immunoassay (EIA) and EBER1/2-RISH, in combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…GC tumor biopsy specimens were obtained from the archives of the VU University Medical Center, Amsterdam, and have been described in earlier studies (40,41). Sections of these tumors were analyzed for the presence of EBV-encoded RNAs (EBERs) by EBER in situ hybridization (EBERish) as described previously (42).…”
Section: Methodsmentioning
confidence: 99%
“…GC tumor biopsy specimens were obtained from the archives of the VU University Medical Center, Amsterdam, and have been described in earlier studies (40,41). Sections of these tumors were analyzed for the presence of EBV-encoded RNAs (EBERs) by EBER in situ hybridization (EBERish) as described previously (42).…”
Section: Methodsmentioning
confidence: 99%
“…GC is one of the most common carcinomas globally, and recent studies revealed the association of EBV with about 10% of GC cases worldwide (Burke et al, 1990;Shibata and Weiss, 1992;Takada, 2000;van Beek et al, 2002). However, the influence of EBV infection on GC development and treatment is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The MeningoFinder assay was compared to routine in-house PCRs. The PCRs for enterovirus, HSV-1, HSV-2, and VZV were performed by PAMM (1,6,15), and the PCRs for CMV and EBV were performed at the Laboratory of Medical Microbiology at the Maastricht University Medical Center (MUMC) (10,16). Viral RNA/DNA from clinical samples (200-l cerebrospinal fluid specimens) for PCR or MLPA was isolated using either the Nuclisense easyMAG (bioMerieux, Boxtel, The Netherlands) or the MagnaPure LC nucleic acid system (Roche Diagnostics) according to the manufacturers' instructions.…”
mentioning
confidence: 99%